Molecular characterization of porcine reproductive and respiratory syndrome virus (PRRSv) identified from slaughtered pigs in northern Uganda - Oba, Peter; Dione, Michel M.; Erume, J.; Wieland, Barbara; Mutisya, Christine; Ochieng, Linnet; Cook, Elizabeth A.J.; Mwiine, F.N. (Springer, 2022)
Background A cross sectional study was conducted to detect and characterize species of porcine reproductive and respiratory syndrome virus (PRRSv) identified from slaughtered pigs in Lira district, northern Uganda. The study was conducted from March to September 2019 in three selected slaughter slabs. Pigs brought for slaughter were randomly sampled. At necropsy, lungs were extracted from the thoracic cavity and examined for pneumonic lesions. Seventy-three (73) pigs with gross lung lesions were sampled, from which one hundred and one (101) tissue samples were taken. A real-time reverse transcriptase PCR (RT-qPCR) was used to characterize PRRSv species.